MEDICINAL PROPERTIES AND GENETIC DIVERSITY OF A MAGICAL SHRUB TINOSPORA CARDIFOLIA: AN UPDATE - PRACHI GUPTA; SAURABH KULSHRESTHA (International Journal of Pharma and Bio Sciences, 2015)
Before the introduction of chemical medicines, man relied on the healing properties of medicinal plants. Perhaps 90% of the world's population still relies completely on raw herbs and unrefined extracts as medicines. Medicinal plants were the “backbone” of traditional medicine, which means more than 3.3 billion people in the less developed countries utilize medicinal plants on a regular basis. Tinospora cardifolia is one of the important medicinal plants which is a large and deciduous climbing shrub found at higher altitudes of India cultivated in tropical areas of India and known by names such as Gurcha, Heart leaved moonseed, Heavenly elixir and Jetwatika. About 152 plants have been documented in India for traditional ayurvedic medicines and out of theses 152 plants; T. cardifolia is one of the most promising plants in the herbal medicine system. The Plant Tinospora includes 76 scientific rank species but only 13 of these species are accepted for medicinal uses. Different parts of T. cardifolia such as leaves, roots and stem are emetic and used in ayurvedic, "Rasayanas" to improve the immune system and the body resistance against infections such as rheumatism, urinary diseases, dyspepsia, general debility, syphilis, skin diseases, bronchitis, spermatorrhea, impotence, general debility, dyspepsia, fevers, urinary diseases, visceral obstruction and leprosy. This review gives a bird view of the main biological activities, pharmacological actions, medicinal applications of T. cardifolia extracts and genetic diversity of T. cardifolia .